1993
DOI: 10.1095/biolreprod48.5.1174
|View full text |Cite
|
Sign up to set email alerts
|

Gelatinolytic and Caseinolytic Proteinase Activities in the Secretions of the Ventral, Lateral, and Dorsal Lobes of the Rat Prostate1

Abstract: The ventral, lateral, and dorsal lobes of the rat prostate produce secretions rich in protein. We examined these secretions for proteinase activities, using gelatin- and casein-containing SDS-polyacrylamide gel zymographies. The ventral lobe demonstrated both higher activities and more molecular forms of proteinase activities that cleaved these two protein substrates than did the other lobes. Ca(2+)-stimulated gelatinolytic activities of approximately 48, 51, 58, 64, 74, and 80 kDa were found in ventral prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 36 publications
(43 reference statements)
0
12
1
Order By: Relevance
“…Matrix metalloproteinases are also found in seminal plasma, where this enzyme plays an important role in keeping the ducts open and in semen liquefaction (Mann & Lutwak‐Mann, 1982). Their presence in prostate secretion was demonstrated by Wilson et al. (1993a,b) and has recently been reinforced by other authors who also found TIMP‐1 and TIMP‐2 in seminal plasma (McCauley et al.…”
Section: Introductionmentioning
confidence: 61%
“…Matrix metalloproteinases are also found in seminal plasma, where this enzyme plays an important role in keeping the ducts open and in semen liquefaction (Mann & Lutwak‐Mann, 1982). Their presence in prostate secretion was demonstrated by Wilson et al. (1993a,b) and has recently been reinforced by other authors who also found TIMP‐1 and TIMP‐2 in seminal plasma (McCauley et al.…”
Section: Introductionmentioning
confidence: 61%
“…The supernatants were collected, determined for protein concentrations by bicinchoninic acid assay using bovine serum albumin (BSA) as standard, and stored at -80°C until subsequent analysis. The cytosolic extracts were separated by electrophoresis in duplicate in 10% SDS-PAGE containing 0.1% gelatin under non-reducing conditions (Heussen and Dowdle 1980;Wilson et al 1988Wilson et al , 1993. About 20 µg unreduced and unboiled proteins dissolved in sample dye (1% phenol red, 2.5% SDS, 1% sucrose and 0.5% glycerin) were added to each lane.…”
Section: Zymography Of Proteasesmentioning
confidence: 99%
“…The rat prostate has been used extensively as a model system to study androgen regulation of growth and function in this gland (Wilson et al, 1993).…”
Section: Introductionmentioning
confidence: 99%